Sediment Yield in Dam-Controlled Watersheds in the Pisha Sandstone Region on the Northern Loess Plateau, China - Fabing Xie (MDPI AG, 2021)
Soil erosion has become the dominant environmental issue endangering sustainable development in agriculture and the ecosystem on the Loess Plateau. Determination of watershed soil erosion rates and sediment yields is essential for reasonable utilization of water resources and soil loss control. In this study, we employed unmanned aerial vehicles (UAVs) and structure-from-motion (SfM) photogrammetry to determine the sediment yields in 24 dam-controlled watersheds in the Pisha sandstone region of the northern Loess Plateau. High differences in total sediment were trapped before the check dams due to their running periods and sediment yields. The estimated specific sediment yield ranged from 34.32 t/(ha∙a) to 123.80 t/(ha∙a) with an average of 63.55 t/(ha∙a), which indicated that the Pisha sandstone region had an intense soil erosion rate. Furthermore, the modified Sediment Distributed Delivery (SEDD) model was applied to identify the erosion-prone areas in the watersheds, and the sediment retained in the check dams were used for model calibration. The performance of the model was acceptable, and the modeling results indicated that the steep Pisha sandstone was the major sediment source for the watersheds, accounting for approximately 87.37% of the sediment yield. Catchment area, erosive precipitation, and badland proportion were the key factors for sediment yield in the dam-controlled watersheds of the Pisha sandstone region, according to multiple regression analyses. These findings indicated that the modified SEDD model is very efficient in identifying spatial heterogeneities of sediment yield in the watershed but requires comprehensive calibration and validation with long-term observations. The Pisha sandstone region is still the key area of soil erosion control in the Loess Plateau, which needs more attention for soil and water conservation due to high sediment yield.